Some aspects of foreign practice in counteracting premeditated murders by criminal police units - Ye. S. Khyzhniak (Bulletin of Kharkiv National University of Internal Affairs)
Some aspects of the international experience in counteracting premeditated murder by criminal police units have been studied. The main factors and features of formation and development of directions in counteraction to premeditated murders have been defined, the available models of counteraction to premeditated murders in activity of police divisions of separate countries have been allocated and analyzed.